A method for enhancing mass transfer of membrane contactor based on falling liquid film flow and a method for calculating the thickness of falling liquid film

By forming a liquid-decreasing film flowing along the film surface in the membrane contactor, the membrane wetting behavior problem caused by amine absorbers is solved, and more efficient and stable CO2 desorption and mass transfer and longer membrane service life are achieved.

CN118179257BActive Publication Date: 2025-04-25NANJING TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410243063.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2025-04-25
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

The membrane wetting behavior caused by amine absorbers leads to poor performance and stability of the membrane contactor during long-term operation, limiting the mass transfer efficiency of the membrane contactor.

Method used

By making the alcohol amine solution form a liquid-decreasing film that disperses downward along the membrane surface on the permeable side of the hydrophilic porous membrane, the membrane pores are wetted with the exuded alcohol amine solution, the mass transfer resistance is reduced, and the separation of gas and liquid phases is promoted.

Benefits of technology

It achieves more efficient and stable CO2 desorption and mass transfer, and the membrane material can be used without modification, which greatly extends the service life of the membrane contactor and significantly improves the mass transfer flux.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118179257B_ABST
    Figure CN118179257B_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing mass transfer of a membrane contactor based on a falling liquid film flow and a method for calculating the thickness of the falling liquid film. The method for enhancing mass transfer of a membrane contactor is to make the alcohol amine solution with CO2 load on the liquid phase side of the hydrophilic porous membrane in the membrane contactor be transmitted in the direction against gravity, and part of the alcohol amine solution continuously seeps out from the membrane pores of the hydrophilic porous membrane, and the falling liquid film formed by the seeped alcohol amine solution on the surface of the hydrophilic porous membrane permeation side, which is dispersed downward and continuously flows along the membrane surface, and the membrane pores that are continuously wetted, are used to reduce the mass transfer resistance, promote the separation of gas-liquid two phases on the permeation side, and timely strip CO2 from the liquid. The membrane contactor is always in a stable operating state during the entire desorption process, and a more efficient and stable CO2 desorption mass transfer is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for enhancing mass transfer of a membrane contactor based on falling liquid film flow and a method for calculating the thickness of a falling liquid film, and belongs to the technical field of membrane separation and enhanced alcohol amine desorption CO2 control. Background Art

[0002] In response to the high energy consumption of CO2 desorption process in the industrial organic alcohol amine method, membrane contactor can use vacuum regeneration technology instead of heating regeneration technology to achieve CO2 desorption. The unit volume of membrane contactor can produce a mass transfer area that exceeds 400-1500% or more of traditional equipment, thereby improving the step of efficient gas-liquid phase transmission in the CO2 desorption process, thereby achieving an increase in desorption flux and a reduction in desorption energy consumption.

[0003] Porous ceramic membranes have great potential in continuous CO2 desorption and separation processes at high temperatures due to their high heat and chemical resistance and mechanical strength. However, the membrane wetting behavior caused by amine absorbents will lead to poor performance stability of membrane contactors during long-term operation, and the internal resistance of the membrane phase will increase significantly, limiting the mass transfer efficiency of the membrane contactor. In order to overcome this instability problem, it is urgent to adopt an innovative strategy based on falling liquid film flow to enhance the mass transfer performance of membrane contactors. Summary of the invention

[0004] The purpose of the present invention is to provide a method for enhancing mass transfer of a membrane contactor based on falling film flow and a method for calculating the thickness of the falling film, so as to solve the problem that the membrane wetting behavior caused by amine absorbents will lead to poor performance stability of the membrane contactor during long-term operation, and propose a method for calculating the thickness of the falling film on a tubular membrane.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for enhancing mass transfer of a membrane contactor based on falling film flow is that when a CO2-loaded alcoholamine solution on the liquid phase side of a hydrophilic porous membrane in a membrane contactor is transmitted in a direction against gravity, part of the alcoholamine solution continuously seeps out from the membrane pores of the hydrophilic porous membrane, and the falling film formed by the seeped alcoholamine solution on the permeation side surface of the hydrophilic porous membrane, which disperses downward along the membrane surface and continuously flows, and the continuously wetted membrane pores, are used to reduce mass transfer resistance and promote separation of gas-liquid phases on the permeation side.

[0007] Preferably, the absorbent used in the alcoholamine solution is an organic alcoholamine compound, selected from monoethanolamine, ethanolamine, triethanolamine, methyldiethanolamine, N,N-diethylethanolamine, 1-dimethylamino-2-propanol, tetraethylenepentylamine, triethylenetetramine, ethylenediamine and other alcoholamines, N-methyldiethanolamine or a mixture of several thereof; the concentration of the organic alcoholamine compound is 1-7 mol / L, preferably 3-5 mol / L.

[0008] Preferably, in the alcoholamine solution, the CO2 loading amount is 0.2-1 mol CO2 / mol absorbent.

[0009] Preferably, the membrane contactor comprises at least one ceramic membrane tube.

[0010] Preferably, the ceramic membrane tube is a single-channel tubular membrane or a multi-channel tubular membrane, with a channel diameter of 4-30 mm and a pore size of 6-20 nm.

[0011] Preferably, the material of the ceramic membrane tube is zirconium oxide.

[0012] Preferably, the membrane contactor is filled with a catalyst, which may be a single catalyst particle or a mixture of different catalysts.

[0013] Preferably, the membrane contactor is also filled with inert particles, which can be selected from inert granular materials such as glass beads, quartz sand and inert ceramic balls.

[0014] Preferably, the temperature of the alcoholamine solution in the membrane contactor is 80-100° C., and the osmotic pressure is 40-70 kPa.

[0015] A method for calculating the thickness of the falling liquid film formed in any of the above methods comprises the following steps:

[0016] The structural characteristics of the hydrophilic porous membrane in the membrane contactor are used to calculate the permeation flux J of a single membrane tube to the alcoholamine solution. The permeation flux J of the alcoholamine solution satisfies the following formula:

[0017]

[0018] Where △P is the transmembrane pressure difference; d m is the average pore size of the membrane; δ is the membrane thickness; ε and τ are the membrane porosity and tortuosity factor, respectively; μ is the viscosity of the alcoholamine solution;

[0019] If the inner side of the hydrophilic porous membrane is the liquid phase side, the falling liquid film is formed on the outer surface of the membrane tube, and the equation is:

[0020] J.S. mo =π[(R mo +X) 2 -R mo 2 ]H m

[0021] At this time, the calculation formula for the thickness X of the falling liquid film is:

[0022]

[0023] Among them, S mo H is the surface area of ​​a single membrane tube of the hydrophilic porous membrane; m , R mo are the effective length and outer diameter of a single membrane tube of the hydrophilic porous membrane in the membrane contactor, respectively;

[0024] If the outer side of the hydrophilic porous membrane is the liquid phase side, then the falling liquid film is formed on the inner surface of the membrane tube, and the equation is:

[0025] J.S. mi =π[R mi 2 -(R mi -X) 2 ]H m

[0026] At this time, the calculation formula for the thickness X of the falling liquid film is:

[0027]

[0028] Among them, S mi H is the inner surface area of ​​a single membrane tube of the hydrophilic porous membrane; m , R mo They are respectively the effective length and inner diameter of a single membrane tube of the hydrophilic porous membrane in the membrane contactor.

[0029] The beneficial effects of the present invention are:

[0030] Under the action of gravity, the alcohol amine solution will form a stable liquid film on the membrane surface of the hydrophilic porous membrane permeation side. This liquid film is constantly moving and updating, and can carry the CO2 desorption gas through the membrane pores and strip CO2 from the liquid in time. The membrane contactor is always in a stable operating state during the entire desorption process, achieving more efficient and stable CO2 desorption mass transfer. The membrane material can be used without modification, which greatly extends the service life of the membrane contactor, and there is no industrial scale-up effect in the process.

[0031] The characteristics of the hydrophilic porous membrane allow the alcohol amine solution to be well dispersed on the membrane surface of the permeation side with a high permeation flux. In theory, the falling liquid film can completely cover the permeation side surface of the hydrophilic porous membrane. The interphase interface of the falling liquid film flow formed on the membrane surface is different from the ideal equilibrium state in the previous mass transfer model. It accelerates the surface renewal rate of the gas-liquid interface in the near-interface region, which makes the effective gas-liquid contact area of ​​the hydrophilic porous membrane higher than that of the hydrophobic membrane, and the mass transfer resistance between the interface and the liquid phase body is greatly reduced, which accelerates the mass transfer between the interface and the liquid phase body. The experimental measurement value of the mass transfer flux in the regeneration process of the alcohol amine rich solution (i.e., the alcohol amine solution loaded with CO2) has increased by 65.8%-158.8% compared with the previous mass transfer process using a hydrophobic membrane, and a good mass transfer flux is maintained in a 20-day continuity test. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the principle of the mass transfer method of the falling liquid film flow enhanced membrane contactor in the present invention;

[0033] Figure 2 It is a comparison chart of CO2 desorption flux using the method of the present invention and using a hydrophobic membrane contactor;

[0034] Figure 3 The effect of the thickness of the liquid film on the mass transfer efficiency of the membrane contactor when the method of the present invention is applied;

[0035] Figure 4 This is a result diagram of a long-term repetitive experiment using the method of the present invention. DETAILED DESCRIPTION

[0036] The present invention relates to a method for enhancing mass transfer of a membrane contactor based on falling liquid film flow, which is mainly used to improve the mass transfer performance of the membrane contactor in the regeneration process of a CO2-rich alcohol amine solution. When the method is applied, the CO2-rich alcohol amine solution first penetrates through the pores of a hydrophilic porous membrane, and then forms a descending thin liquid film that flows along the vertical wall and is evenly dispersed under the action of gravity and interfacial shear force and covers the membrane surface on the permeation side. This layer of liquid film fluctuates near the permeation side surface of the membrane and keeps constantly updated. During the entire mass transfer process, the membrane pores are completely infiltrated by the alcohol amine solution, and the gas flows to the permeation side through the membrane pores without selectivity. The falling liquid film method not only retains the advantage of a high gas-liquid contact area, but also effectively avoids the problem of large mass transfer resistance in the wetting pores in the traditional hydrophobic membrane desorption method. The method greatly improves the mass transfer efficiency of the membrane contactor and realizes more efficient CO2 desorption and mass transfer. The ceramic membrane material of the present invention can be used without modification, and the membrane contactor has good operating stability and good industrial application prospects.

[0037] like Figure 1 As shown, the present invention proposes a method for obtaining CO2 in alcohol amine rich solution based on descending liquid film flow-enhanced ceramic membrane contactor mass transfer. The process occurring in the membrane contactor is as follows: the alcohol amine rich solution is pumped into the shell side of the membrane contactor, the feed liquid first permeates through the porous membrane pores, and then forms a descending liquid film on the membrane permeation side surface under the action of gravity, the hydrophilic and porous characteristics of the ceramic membrane allow the alcohol amine solution to be well dispersed on the membrane surface with a high permeation flux, and the CO2 desorption gas penetrates the membrane layer together with the alcohol amine solution into the permeation side of the membrane contactor, and the gas-liquid two-phase separation is achieved on the liquid membrane surface.

[0038] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.

[0039] Example 1

[0040] (1) A tubular ceramic membrane with an average pore size of 10 nm was washed three times with deionized water and ethanol, and dried in an oven at 110°C for 12 hours, thereby effectively removing dust and other pollutants on the membrane surface and in the membrane pores;

[0041] (2) Assembling a membrane contactor with the tubular ceramic membrane pretreated in step 1, placing the membrane contactor vertically, and building a membrane desorption system;

[0042] (3) The solutions used were all prepared by mixing deionized water and chemical reagents in a certain ratio, and the reagents used were all freshly prepared. A MEA solution with a concentration of 5 mol / L was prepared, and carbon dioxide was introduced into the solution, with a CO2 loading of approximately 0.45 mol / mol MEA;

[0043] (4) After reaching the set temperature of 95°C, start the liquid pump. After the temperature of the entire membrane desorption device system is stable, start the vacuum pump to control the descending liquid membrane flow rate, and set the permeate side pressure to 80, 70, 60 and 50 kPa (absolute pressure) respectively;

[0044] (5) When the system starts working, the amine-rich solution is pumped into the membrane contactor tube side at a feed rate of 300 mL / min. The mass flow rate of CO2 is measured and recorded using a gas mass flow meter. The CO2 gas permeation flux is calculated to be 3.14 L / (m 2 ·h)、8.03L / (m 2 ·h)、12.39L / (m 2 ·h)、13.44L / (m 2 h).

[0045] Example 2

[0046] (1) A tubular ceramic membrane with an average pore size of 10 nm was washed three times with deionized water and ethanol, and dried in an oven at 110°C for 12 hours, thereby effectively removing dust and other pollutants on the membrane surface and in the membrane pores;

[0047] (2) Assembling a membrane contactor with the tubular ceramic membrane pretreated in step 1, placing the membrane contactor vertically, and building a membrane desorption system;

[0048] (3) The solutions used were all prepared by mixing deionized water and chemical reagents in a certain ratio, and the reagents used were all freshly prepared. A MEA solution with a concentration of 5 mol / L was prepared, and carbon dioxide was introduced into the solution, with a CO2 loading of approximately 0.45 mol / mol MEA;

[0049] (4) After reaching the set temperature of 95°C, start the liquid pump. After the temperature of the entire membrane desorption device system stabilizes, start the vacuum pump and set the permeate side pressure to 60 kPa (absolute pressure);

[0050] (5) When the system starts working, the amine rich liquid is pumped into the membrane contactor tube side at a flow rate of 100 mL / min to 500 mL / min. The calculated liquid film thickness is 1.10 mm, 1.14 mm, 1.18 mm, 1.25 mm and 1.35 mm. The mass flow rate of CO2 is measured and recorded by a gas mass flow meter, and the CO2 gas phase mass transfer rates are 0.81 mol / h, 0.099 mol / h, 0.140 mol / h, 0.148 mol / h and 0.158 mol / h, respectively.

[0051] The thickness of the falling liquid film is determined by two methods: experimental measurement and theoretical calculation, and the error between the two methods does not exceed 3%.

[0052] Method 1: Based on the calculation formula of the thickness X of the falling liquid film:

[0053]

[0054] As the liquid phase flow rate changes, ΔP changes accordingly. The flow rate increases from 100mL / min to 200mL / min, 300mL / min, 400mL / min and 500mL / min, and the corresponding values ​​of ΔP are 42.4kPa, 44.2kPa, 46.1kPa, 48.2kPa and 51.8kPa respectively; d m ,δ,ε,τ,H m , R mo The parameters are determined according to the specifications of the membrane and membrane contactor, which are 10nm, 40μm, 0.38, 2.0, 300mm, 12mm respectively; μ is the viscosity of the alcohol amine solution 0.55mPa.s. The calculated liquid film thicknesses are 1.10mm, 1.14mm, 1.18mm, 1.25mm and 1.35mm respectively.

[0055] Method 2: The permeation volume V of the amine solution was measured experimentally to calculate the permeation flux J, and then the liquid film thickness was calculated based on material balance. The flow rate increased from 100 mL / min to 200 mL / min, 300 mL / min, 400 mL / min and 500 mL / min, and the obtained liquid film thicknesses were 1.07 mm, 1.12 mm, 1.19 mm, 1.24 mm and 1.33 mm, respectively.

[0056] Comparative Example 1

[0057] (1) Different from Example 1, a hydrophobic membrane contactor is used here. The first step is to prepare a hydrophobic membrane. The single-channel tubular ceramic membrane is hydrophobically modified by surface grafting modification. The modified liquid is fully stirred in a 30°C water bath. The ceramic membrane is then placed in the prepared modified solution and vacuumed until no bubbles are generated on the membrane surface. The taken-out ceramic membrane is washed three times with deionized water and ethanol, placed in an oven, and dried at 110°C for 12 hours to obtain a ceramic membrane with good hydrophobic properties.

[0058] (2) Same as step 2 of Example 1;

[0059] (3) Same as step 3 of Example 1;

[0060] (4) Same as step 4 in Example 1;

[0061] (5) When the system starts working, the amine-rich solution is pumped into the membrane contactor tube side at a feed rate of 300 mL / min. The mass flow rate of CO2 is measured and recorded using a gas mass flow meter. The CO2 gas permeation flux is calculated to be 3.12 L / (m 2 ·h)、3.98L / (m 2 ·h)、4.79L / (m 2 h)、5.95L / (m 2 h).

[0062] The comparison of CO2 desorption flux under the same conditions between the membrane contactor used in Example 1 and the hydrophobic membrane contactor used in Comparative Example 1 is shown in the figure. Figure 2 As shown. Figure 2 It can be seen that at the permeate side pressure of 50 kPa, 60 kPa, and 70 kPa, the mass transfer flux of the membrane contactor based on the falling liquid film method increased by 125.8%, 158.66%, and 101.76%. According to the method provided in Example 1, repeated desorption experiments were continuously carried out under the same operating conditions, and it was found that the desorption performance did not change significantly, and the permeate flux was maintained at more than about 95%. The results are shown in the attached Figure 4 .

[0063] Comparative Example 2

[0064] (1) The difference from Example 2 is that in this comparative example, a small desorption device is used and a conventional desorption method is adopted to regenerate the alcoholamine rich solution, and no membrane contactor is involved;

[0065] (2) The solutions used were all prepared by mixing deionized water and chemical reagents in a certain ratio, and the reagents used were all freshly prepared. A MEA solution with a concentration of 5 mol / L was prepared, and carbon dioxide was introduced into the solution, with a CO2 loading of approximately 0.45 mol / mol MEA;

[0066] (3) After reaching the set temperature of 95°C, the system starts to work, and the amine rich solution is pumped in at a flow rate of 100 mL / min to 500 mL / min. The mass flow rate of CO2 is measured and recorded using a gas mass flow meter, and the CO2 gas phase desorption mass transfer rates are 0.016 mol / h, 0.027 mol / h, 0.048 mol / h, 0.053 mol / h and 0.060 mol / h, respectively.

[0067] In order to evaluate the mass transfer efficiency of the falling film membrane contactor, the mass transfer efficiency using the desorption method in Example 2 was compared with the mass transfer efficiency using the conventional desorption method in Comparative Example 2, and the mass transfer equivalent factor was selected as the mass transfer performance evaluation index.

[0068] The mass transfer equivalent factor η is defined as: under the same desorption conditions, the ratio of the mass transfer efficiency of the membrane area to the mass transfer efficiency of the conventional desorption area for desorption of the same mole of CO2 gas per unit time. Its definition is:

[0069]

[0070] Among them, G m and G c are the CO2 gas phase mass transfer rates under membrane desorption conditions and conventional desorption conditions, respectively; Sm and Sc are the membrane area and the mass transfer area of ​​the conventional desorption equipment.

[0071] like Figure 3As shown, compared with the mass transfer efficiency under the conventional desorption method in Comparative Example 2, under different falling liquid film thicknesses (theoretical calculated thickness) in Example 2, the values ​​of the mass transfer equivalent factors of the membrane contactor based on the falling liquid film method are 0.37, 0.51, 0.64, 0.66 and 0.70, respectively. It can be seen from the analysis that the falling liquid film is applied to flow to the ceramic membrane contactor to enhance the mass transfer process, and the desorbed gas will flow to the permeate side with the alcohol amine liquid through the membrane pores without selectivity. This method significantly improves the mass transfer efficiency of the membrane contactor interface, and the entire desorption process is always in a stable operating state. During the entire experimental process, the flow rate of the falling liquid film can be controlled by controlling the process conditions, and the mass transfer performance of the membrane contactor is improved to varying degrees with the process conditions. The mass transfer equivalent factor of the membrane contactor is compared with the mass transfer efficiency of conventional desorption on traditional equipment with the same mass transfer area. According to the results of Example 2, the mass transfer equivalent factor of the membrane contactor can reach 0.70 when the falling liquid film method is applied to the membrane contactor. This proves that the method of mass transfer based on falling film flow-enhanced ceramic membrane contactor provided by the present invention has good application prospects in the field of membrane CO2 capture technology. This result also proves that the mass transfer efficiency of the falling film membrane contactor is high and has the potential to replace conventional desorption equipment. Conventional desorption equipment obtains a larger mass transfer area by increasing the size of the equipment, while the membrane contactor can provide a larger mass transfer area per unit volume; that is, through reasonable design, better desorption performance can be achieved compared to conventional desorption equipment. Therefore, the falling film membrane contactor we proposed is of great significance for reducing the size of heat and mass transfer components and reducing equipment costs.

[0072] Comparative Example 3

[0073] (1) Same as step 2 of Example 1;

[0074] (2) Assembling a membrane contactor with the tubular ceramic membrane pretreated in step 1 to build a membrane desorption system. Different from Example 1, the placement of the membrane contactor is changed from vertical placement to horizontal placement;

[0075] (3) Same as step 3 of Example 1;

[0076] (4) Same as step 4 in Example 1;

[0077] (5) When the system starts working, the amine-rich liquid is pumped into the shell of the membrane contactor at a feed rate of 300 mL / min. At this time, a flowing liquid film cannot be formed on the membrane surface, and the liquid in the membrane tube gradually accumulates to form a "liquid seal" state. The separation and mass transfer performance decreases rapidly until the mass transfer capacity is lost.

[0078] In summary, the method for mass transfer of a membrane contactor based on falling film flow enhancement provided by the present invention can carry CO2 desorption gas through the membrane pores and strip CO2 from the liquid in time through the continuous movement and renewal of the falling film formed by the alcohol amine solution on the membrane surface on the permeation side of the hydrophilic porous membrane under the action of gravity. The membrane contactor is always in a stable operating state during the entire desorption process, achieving more efficient and stable CO2 desorption mass transfer.

[0079] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A method for enhancing mass transfer in a membrane contactor based on falling film flow, characterized in that: When the alcoholamine solution with CO2 loading on the liquid phase side of the hydrophilic porous membrane in the membrane contactor is transmitted in the direction against gravity, part of the alcoholamine solution continuously seeps out from the membrane pores of the hydrophilic porous membrane, and the falling liquid film formed by the seeped alcoholamine solution on the permeation side of the hydrophilic porous membrane, which disperses downward along the membrane surface and continuously flows, and the continuously wetted membrane pores, is used to reduce the mass transfer resistance, thereby promoting the separation of gas-liquid two phases on the permeation side; The method for calculating the thickness of the formed falling liquid film comprises the following steps: The structural characteristics of the hydrophilic porous membrane in the membrane contactor are used to calculate the permeation flux J of a single membrane tube to the alcoholamine solution. The permeation flux J of the alcoholamine solution satisfies the following formula: Where △P is the transmembrane pressure difference; d m is the average pore size of the membrane; δ is the membrane thickness; ε and τ are the membrane porosity and tortuosity factor, respectively; μ is the viscosity of the alcoholamine solution; If the inner side of the hydrophilic porous membrane is the liquid phase side, the falling liquid film is formed on the outer surface of the membrane tube, and the equation is: J·S mo =π[(R mo +X) 2 -R mo 2 ]H m At this time, the calculation formula for the thickness X of the falling liquid film is: Among them, S mo H is the surface area of ​​a single membrane tube of the hydrophilic porous membrane; m , R mo are the effective length and outer diameter of a single membrane tube of the hydrophilic porous membrane in the membrane contactor, respectively; If the outer side of the hydrophilic porous membrane is the liquid phase side, then the falling liquid film is formed on the inner surface of the membrane tube, and the equation is: J·S mi =π[R mi 2 -(R mi -X) 2 ]H m At this time, the calculation formula for the thickness X of the falling liquid film is: Among them, S mi H is the inner surface area of ​​a single membrane tube of the hydrophilic porous membrane; m , R mo They are respectively the effective length and inner diameter of a single membrane tube of the hydrophilic porous membrane in the membrane contactor.

2. The method for mass transfer in a membrane contactor based on falling film flow enhancement according to claim 1, characterized in that: The absorbent used in the alcoholamine solution is an organic alcoholamine compound, and the concentration of the organic alcoholamine compound is 1-7 mol / L.

3. The method for mass transfer intensified membrane contactor based on falling film flow according to claim 1, characterized in that: In the alcohol amine solution, the CO2 loading amount is 0.2-1 mol CO2 / mol absorbent.

4. The method for mass transfer intensified membrane contactor based on falling film flow according to claim 1, characterized in that: The membrane contactor comprises at least one ceramic membrane tube.

5. The method for mass transfer intensified membrane contactor based on falling film flow according to claim 4, characterized in that: The ceramic membrane tube is a single-channel tubular membrane or a multi-channel tubular membrane, with a channel diameter of 4-30 mm and a pore size of 6-20 nm.

6. The method for mass transfer in a membrane contactor based on falling film flow enhancement according to claim 4, characterized in that: The material of the ceramic membrane tube is zirconium oxide.

7. The method for mass transfer in a membrane contactor based on falling film flow enhancement according to claim 1, characterized in that: The membrane contactor is filled with a catalyst.

8. The method for mass transfer intensified membrane contactor based on falling film flow according to claim 7, characterized in that: The membrane contactor is also filled with inert particles.

9. The method for mass transfer intensified membrane contactor based on falling film flow according to claim 1, characterized in that: The temperature of the alcohol amine solution in the membrane contactor is 80-100° C., and the pressure on the osmotic side is 40-70 kPa.

Citation Information

Patent Citations

  • Method for separating methane, methane separator and methane utilization system

    CN101415803A